Usage of blackboard learn for teaching and learning in the historically disadvantaged institution: Challenges and prospects - Maluleke, W. (South African Journal of Higher Education, 2024)
The utilisation of online platform Blackboard Learn for Teaching and Learning (T & L) has become an essential and obligatory component of Higher Education Institutions (HEIs). This study research aims to examine the difficulties and potential of its implementation at a Historically Disadvantaged Institution (HDI) like University of Limpopo (UL), with a focus on the Bachelor of Arts (BA) programme in Criminology and Psychology (Crim & Psych) as guided by University of Limpopo Faculty of Humanities Multimodal Teaching and Learning Plan (UL FHMTLP). This qualitative study employed an empirical research design, selecting Twelve (12) permanent Academics/Lecturers from the Department of Criminology and Criminal Justice at UL for interview purposes. The verbatim responses from the interviews were analysed to identify the key themes and sub-themes of the study using the inductive Thematic Content Analysis (TCA) method. This study revealed that there is a lack of utilisation of Blackboard Learn at UL, as well as ineffective adaptation of current strategies and UL FHMTLP implementations. Many Lecturers still depend on contact T & L and the use of Blackboard Learn to connect the operations of this programme is currently unsuccessful. Recommendations consist of regular training and refreshment courses on the application of this technology, such as the Learning Management System (LMS) provided by the Information and Communications Technology [ICT]-electronic-(e)-Learning Unit. This could potentially facilitate collaborations between Natural Sciences (Technology ‒ Blackboard Learn) and Human Sciences (Crim & Psych) to generate new knowledge, while also clearly providing the advantages of technology utilisation for T & L at UL. This kind of innovation could accommodate “economical, educational, technical, and social transformations” to address the mentioned challenges and opportunities, while making contributions to the field of professorship, with a focus on the South African Future Professors Programme (FPP) Phase 2 Cohort 1 2022‒2023, utilising Blackboard Learn for T & L in a HDI to outline the existing challenges and possibilities.